FIRST EXPERIENCE OF CAGE CULTIVATION OF HATCHERY-PRODUCED JUVENILE SCALLOP MIZUHOPECTEN YESSOENSIS AT EASTERN COAST OF PRIMORYE - S. G. Gavrilova; I. Yu. Sukhin; I. S. Turabzhanova (Известия ТИНРО, 2019)
Yesso scallop Mizuhopecten yessoensis is the main object of aquaculture in Primorye with annual yield measured in hundreds ton. However, further development of its farming could be restricted by lack of the spat. Availability of the spat imported from China using for the scallop cultivation at the coast of Primorye is explored. The spat from Chinese hatchery located in Shandong province was supplied for one aquaculture company in Primorye in the volume of 660 . 106 ind. in 2018 and settled to hanging collectors (1000 ind. per bag), then to cages in the marine farm located north-eastward from the Moryak-Rybolov Bay. Survival and growth rate of the scallop juveniles were examined in early November 2018, when the water temperature was from 10.3–10.4 оС at the sea surface to 9.7–9.9 оС at the bottom, salinity was about 33.60 psu in the whole water column, chlorophyll a concentration varied in the range 0.4–0.8 mg/L with the maximum in the layer 8–24 m. The spat mortality during transportation was estimated as 15 %, but it increased to 56–90 % during its growing up in cages. This level of mortality is much higher than mortality of the spat collected from the coastal waters at southern Primorye. The highest mortality of artificial spat was observed for large-sized mollusks, whereas it was satisfactory for the small-sized ones. Possible reason of high mortality is too high density of juveniles and damaging of their soft tissues by other shells. The spat shells height did not exceed 5–10 mm in the collectors but increased during their growing in cages to 20–25 mm. This size is similar to the size of scallop growing from natural spat in southern Primorye. However, growth rate of the scallop growing at the Moryak-Rybolov Bay (2.0–2.7 mm/month) is lower than in Peter the Great Bay (3.0–3.5 mm/month) though higher than in the Vladimir Bay and Aniva Bay. Mean body weight of the cultivated scallop in November was 1.5 ± 0.1 g.